Refracted Gazes: A Woman Photographer during Mandate Lebanon (Altre Modernità, 2012)
The fall of the Ottoman Empire and the establishment of the French Mandate created many conflicts and much debate in the Middle East region. The paper will attempt to answer the following questions: How were these conflicts in the context of Lebanon represented through Marie al-Khazen’s (1899-1983) photographs? What does the change in pose and attire signify within an emerging culture caught between the two imperial powers of the Ottoman Empire and the French mandate? And where can ‘modernity’ be located between the rural subject and the urban subject? Unlike the mainstream representational strategies of Middle Eastern women which were structured around white male European fantasies of the sort that circulated widely at the turn of the Twentieth-Century in images such as Marie Lydie Bonfils’s (1837-1919) bedouin woman, in Marie al-Khazen’s photographs, women projected a local female subjectivity. This paper explores the relationship between modernity and femininity as manifest through the women’s activity, gaze and attire in Marie al-Khazen as well as other photographs taken in the Middle East region between the 1930s and the 1940s. Al-Khazen and the women represented in the photographs of this period were part of a cosmopolitan sensibility that reveals the Middle East region to be far more international than one might have imagined. Caught between projecting a self-image of the cosmopolitan woman and one of the traditional bedouin, these photographs provide a rich field for tracking the ambiguities of the modern.